Pelayanan NIB Melalui Inovasi GAMPIL DPMPTSP Kab. Bantul - Eka Ina Aulia; Nursaputri, Esti; Rochmadi, Tri (LPPM POLITEKNIK LP3I, 2024)
Business legality is an important aspect that shows legal recognition of a business entity, especially for Micro, Small, and Medium Enterprises (MSMEs). In an effort to increase awareness and ease for business actors in obtaining legality, the Bantul Regency Investment and One-Stop Integrated Service Office (DPMPTSP) launched the GAMPIL (Direct Licensing Service Movement) innovation program. This program aims to direct the licensing process through the publication of a Business Identification Number (NIB) quickly and efficiently. NIB not only functions as a single identity for business actors according to the 2020 KBLI classification, but also replaces various other business permits, such as Company Registration Certificates (TDP) and Import Identification Numbers (API), and facilitates export access. The program implementation method uses the Participatory Action Research (PAR) approach, involving three main stages: research, action, and community participation. This program has been implemented in 18 villages with the support of the Special Fund, resulting in 713 NIBs being issued in a short time. Evaluation of the program showed success in various indicators, including high community participation (95%), efficiency of the NIB creation process (average 1 hour), and participant satisfaction level of 90%. In addition to administrative benefits, the GAMPIL program also has a positive impact on community economic empowerment, increasing the competitiveness of MSMEs, and creating a favorable investment climate in the Regency. The GAMPIL program has proven the effectiveness of integrated licensing services such as OSS in accelerating the business legality process and encouraging formal economic participation. With satisfactory results, this program is expected to continue, expand its reach, and become a model for other regions to create fast, easy, and sustainable licensing services to support local economic growth.